Health Human Performance (Texas Journal of Medical Science, 2022)
More than anything, people want good health. Health is the number one issue. Great, but have you tried to define what health really means? And also in this article we will look at various diseases that occur during the activity of a person and his health, how to maintain health and many similar processes.